Identification of Chlamydophila abortus infection in aborting ewes and goats in Eastern Turkey - Kalender, H.; Kilic, A.; Eroksuz, H.; Muz, A.; Kilinc, U.; Tasdemir, B. (Ecole Nationale Veterinaire Toulouse, 2013)
This study was conducted to identify Chlamydophila abortus (C. abortus) by culture and PCR in aborting ewes and goats. During two successive lambing seasons, a total of 71 aborted foetuses (64 sheep and 7 goats, each from a different herd), and 100 vaginal swab samples from 10 of the herds in which abortions had been observed, have been analysed by culture and PCR. C. abortus was identified in 7 (6 lambs and 1 goat) of the 71 aborted foetuses (9.86%) using culture and PCR from embryonated egg yolk sacs inoculated with foetal organ suspensions, and was detected directly from foetal organ suspensions in only 5 cases. The C. abortus DNA was also identified in 6% of the vaginal swab samples as well as in the corresponding abortion products in 2 of the herds. All isolates showed identical restriction profiles with the S26/3 reference strain using Alu1 and HaeIII restriction enzymes in the Restriction Fragment Length Polymorphism (RFLP) test. Focal necrosis was evidenced in foetal liver, spleen and lungs, as well as portal mononuclear cell infiltrates in the liver and alveolar septal thickening in the lungs. These findings show that C. abortus plays a substantial role in sheep abortion in Turkey.
Keywords: Chlamydophila abortus; ewe; goat; abortion; culture isolation; PCR; RFLP; Turkey